EVALUASI RENCANA SEMPADAN SUTT DAN SUNGAI MAHAKAM KOTA SAMARINDA (Studi Kasus Kecamatan Sungai Kunjang) - , AGRIALDY H. PRADANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Demarcation line is a safety outer perimeter that set to build a building or fence withdrawn at a certain distance parallel to road, outer edge of the bridge head, riverside, edge of the channel, foot embankment, the edge of the swamp, the reservoirs, the edge of the springs, railroads, electricity network and gas pipeline, depends on the list of the demarcation line types. Outside the perimeter, the owner of the land is not allowed to build a building. But in real life there are many regions that build buildings inside the perimeter, such as Sungai Kunjang Subdistrict of Samarinda City. The purpose of this research is to know the implementation of the demarcation of High-Tension Transmission Lines and Mahakam Riparian whether it is appropriate or not This research using explorative deductive method. With this method, the writer can get the results based on facts through observation and interview. The results of this research is the existing condition is not in accordance with the direction of the plan. For High-Tension Transmission Lines demarcation, there are many buildings near the tower inside the perimeter and for riparian there are buildings that half of the buildings is on the river. The government of Samarinda City should be more strict when is about to give building permits. So the misuse land problem inside the perimeter can be minimalized.